Penerapan Akuntansi Persediaan Berbasis SAK EMKM Pada UD Andika Jaya Jember - Cahyanti Hana Pratiwi (COSTING : Journal of Economic, Business and Accounting, 2018)
In trading companies, inventory is a valuable resource because it becomes a larger asset than the current assets. Therefore, the main income of the company comes from the sale of goods from inventory. Therefore, accounting management for inventory is important to avoid fraud. The data for this paper is provided by a trading company that provides a basic need for consumers to implement a reliable inventory management. The object of this paper is the name of his company UD Andika Jaya Jember. This paper uses descriptive qualitative method. The paper concludes that UD Andika Jaya Jember has implemented accountability based on their inventory management but still needs improvement on the provision of workload sharing to enter and store goods and revenues. Keyword : Inventory, Accounting, Management